Analisis Kausalitas Kecelakan Konstruksi dengan Pendekatan Analogi Fault Tree Analysis (FTA) - Adwitya Bhaskara; Cahyo Dita Saputro; Firdamarsha Benadikta; Syawaluddin Alim; Danny Setiawan (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2021)
In mid-2019, there was a construction accident during the underpass construction project in Yogyakarta. The underpass excavation wall in this project was collapsed and 2 vehicles were reported fallen. Although such accident sometimes occurs in some projects, it does not mean that these accidents are caused by the same source. Many efforts to prevent accidents have been done by various methods and one of them is an assessment by observation at construction sites referring to Government Regulation 05 2014 concerning SMK3 (Occupational Safety and Health Management System) in the Public Works Sector Construction. The details about the implementation of construction work are described in PUPR Decree No. 21 in 2019 in term of the Construction Safety Management System (SMKK) Guidelines. This research was conducted to identify factors and indicators of management consultants, supervisors and contractors who have a major impact and contribution to the underpass construction project in Kentungan, Yogyakarta. The percentage level of accuracy in the application of the construction safety management system based on the assessment of the contractor was 85.938% and for the supervisory consultant the percentage level of accuracy was 97.29%. Both percentages are included in the satisfactory category since the assessment ranges are between 85% and 100%. Based on these two assessments, an evaluation was carried out using a Fault Tree Analysis to determine the causality flow of construction accidents.